Species composition of fishes assemblage in shatt Al-Basrah canal, South of Iraq - Younis, K. H.; AL-Shamary, A. CH. (Iraqi Journal of Aquaculture, 2022)
The fish assemblage structure in Shatt AL-Basrah canal was described during the period June 2008–June 2009. Two stations were chosen, the first at the upper reaches of the Canal south to the regulation Dam and the second station located near AL-Zubair Bridge. We collected 51 species belonging to Osteichthyes and two species to Chondrichthyes.The number of species collected was 38 species in both stations. The total number of individuals collected was 8216 in the first station and 2969 fish in the second station. The Similarity index in the species composition of the fish assemblage was 49% between the two stations. Diversity (H), Evenness (J) and Richness (D) of the fish assemble was respectively 2.57, 0.71, 4.63 in the first station .while at the second station was lower 2.06, 0.57, 4, 10 respectively.